Economic Growth and Local Own-source Revenue towards Regional Financial Independence - Asyari Rosidin; Acwin Hendra Saputra (Universitas Gorontalo, 2020)
This research aims to determine the effect of economic growth and local revenue on the level of regional financial independence in districts/cities in East Java province for the period 2006-2016. This study's secondary data sources came from Statistics Indonesia (BPS) and The Audit Board of Indonesia (BPK RI) audit reports. We choose the panel data analysis technique to provide more information, more variation, less co-linearity between variables, more degree of freedom, and more efficiency. The results showed that the variables of economic growth and local own-source revenue, either alone or together, had a significant positive effect on the level of regional financial independence.